1984
DOI: 10.1093/nar/12.23.9165
|View full text |Cite
|
Sign up to set email alerts
|

Infrared linear dichroism of oriented DNA-ligand complexes prepared with the wet-spinning method

Abstract: Oriented DNA films prepared by the wet-spinning technique have been complexed with several ligands: the anthracycline antibiotic violamycin BI, the dipeptide L-carnosine, and the oligopeptide antibiotic netropsin. The formation of the DNA-ligand complexes is accompanied by dramatic changes of the conformational flexibility of DNA. The B-A transition which occurs usually between 80% and 70% relative humidity (RH) is more or less suppressed by the ligands. Violamycin BI at a total ligand per DNA base pair ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…This is indicated by farily high values of 9 0 p 0 at reduced RH, usually measured at 76% RH. As reported previously, the netropsinDNAcomplex is almost completely in the B form at76% RH if the inputratio(drug/ DNA base pair) is 0.2 (8). This result, however, holds for CT-DNA (42% GC).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…This is indicated by farily high values of 9 0 p 0 at reduced RH, usually measured at 76% RH. As reported previously, the netropsinDNAcomplex is almost completely in the B form at76% RH if the inputratio(drug/ DNA base pair) is 0.2 (8). This result, however, holds for CT-DNA (42% GC).…”
Section: Resultssupporting
confidence: 54%
“…Oriented films ofNaDNA were obtained by the wetspinning technique as described elsewhere (8,15,16). Details of the measurement and of the quantitative determination ofB-and A-DNA in a mixture ofboth conformations were given elsewhere (7 ,8,1 0) and will not be repeated in detail here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared (IR) linear dichroism studies have shown the potency of several drugs to suppress the B-A transition of DNA stretches much longer than the binding site of the drug on DNA (13)(14)(15)(16)(17). Depending on the relative drug concentration, a substantial fraction of DNA was shown to lose its conformational flexibility and to remain in the B form even at RHs below 75 %.…”
Section: Introductionmentioning
confidence: 99%
“…The related non-intercalating compound netropsin exhibits a similar behavior ("freezing" of the B conformation, Fritzsche et a1. 43,44). However, pentamidine, with its bulkier, more flexible, and longer aliphatic chain ( -O(CH2)50 -), positioned closely at the surface of the groove, is not able to suppress the B + C transition of the host duplex.…”
Section: Discussionmentioning
confidence: 99%